One day in December : a novel - Silver, Josie (New York : Ballantine Books, 2020)
"Laurie is pretty sure love at first sight doesn't exist anywhere but the movies. But then, through a misted-up bus window one snowy December day, she sees a man who she knows instantly is the one. Their eyes meet, there's a moment of pure magic... and then her bus drives away. Certain they're fated to find each other again, Laurie spends a year scanning every bus stop and cafe in London for him. But she doesn't find him, not when it matters anyway. Instead they "reunite" at a Christmas party, when her best friend Sarah giddily introduces her new boyfriend to Laurie. It's Jack, the man from the bus. It would be. What follows for Laurie, Sarah and Jack is ten years of friendship, heartbreak, missed opportunities, roads not taken, and destinies reconsidered. One Day in December is a joyous, heartwarming and immensely moving love story to escape into and a reminder that fate takes inexplicable turns along the route to happiness."--Cover
Keywords: Man-woman relationships -- Fiction; Love stories